Transformasi Pendidikan Islam Di Era Globalisasi Dan Teknologi: Tantangan Dan Solusi - Muhammad Ilyas; Sukari (4, 2024)
The transformation of Islamic education in the era of globalization and the development of information technology has become an urgent need to remain relevant to changing times. Globalization brings challenges such as information transparency, cultural plurality, and increasingly fierce global competition. Meanwhile, information technology presents significant opportunities to expand access to education, improve the quality of learning, and introduce innovation in teaching methods. Islamic education serves not only as a means of transmitting religious values ​​but also as a strategic medium for shaping a generation with faith, noble character, and 21st-century skills. Integrating technology into the learning process is a key step, where technology acts as an interactive medium that can increase learning effectiveness while enriching students' learning experiences. The study revealed that the main challenges in the transformation of Islamic education include the gap in technology access between educational institutions, low digital literacy among both educators and students, limited supporting infrastructure, and a curriculum that is not yet fully adapted to global needs. However, on the other hand, emerging opportunities include the ability to utilize technology for online learning, the development of digital literacy, and the strengthening of multicultural education relevant to the context of a pluralistic global society. As a solution, concrete strategies are needed in the form of formulating an adaptive curriculum, intensive training for educators in the use of technology, providing adequate digital infrastructure, and internalizing multicultural values ​​based on Islamic teachings. Abstrak Transformasi pendidikan Islam di era globalisasi dan perkembangan teknologi informasi menjadi suatu kebutuhan mendesak agar tetap relevan dengan perubahan zaman. Globalisasi membawa tantangan berupa keterbukaan informasi, pluralitas budaya, serta kompetisi global yang semakin ketat. Sementara itu, teknologi informasi menghadirkan peluang besar dalam memperluas akses pendidikan, meningkatkan kualitas pembelajaran, dan menghadirkan inovasi dalam metode pengajaran. Pendidikan Islam tidak hanya berfungsi sebagai sarana pewarisan nilai-nilai keagamaan, tetapi juga sebagai media strategis untuk membentuk generasi yang beriman, berakhlak mulia, serta memiliki keterampilan abad ke-21. Integrasi teknologi dalam proses pembelajaran menjadi langkah utama, di mana teknologi berperan sebagai medium interaktif yang mampu meningkatkan efektivitas pembelajaran sekaligus memperkaya pengalaman belajar peserta didik. Hasil kajian menunjukkan bahwa tantangan utama dalam transformasi pendidikan Islam mencakup kesenjangan akses teknologi antara lembaga pendidikan, rendahnya literasi digital di kalangan pendidik maupun peserta didik, keterbatasan infrastruktur pendukung, serta kurikulum yang belum sepenuhnya adaptif dengan kebutuhan global. Namun, di sisi lain, peluang yang muncul antara lain kemampuan memanfaatkan teknologi untuk pembelajaran daring, pengembangan literasi digital, serta penguatan pendidikan multikultural yang relevan dengan konteks masyarakat global yang plural. Sebagai solusi, dibutuhkan strategi konkret berupa perumusan kurikulum adaptif, pelatihan intensif bagi pendidik dalam pemanfaatan teknologi, penyediaan infrastruktur digital yang memadai, serta internalisasi nilai multikultural yang berpijak pada ajaran Islam.